设随机变量X的分布律为[img=156x60]18031e91408e27e.png[/img]k=0,1,2,... 则a的值为( ).
A: 1
B: [img=25x22]18031e91489ad35.png[/img]
C: e-l
D: el
A: 1
B: [img=25x22]18031e91489ad35.png[/img]
C: e-l
D: el
C
举一反三
- 设随机变量X的分布律为[img=156x60]17de7ed1c30facb.png[/img]k=0,1,2,...,n,则a的值为( ). 未知类型:{'options': ['1', '', 'e-l', 'el'], 'type': 102}
- 设随机变量X的分布律为[img=156x60]1802f281ec918d9.png[/img]k = 0, 1, 2, ..., n,则a的值为( ). 未知类型:{'options': ['1', '', 'e-l', 'el'], 'type': 102}
- 设随机变量X的分布律为[img=156x60]17de92215f99629.png[/img],k=0,1,2,...,n,则a的值为( ). 未知类型:{'options': ['1', '1/e', '', ''], 'type': 102}
- 设随机变量X的分布律为[img=156x60]1803b452229ab83.png[/img],k=0,1,2,...,n,则a的值为( ). 未知类型:{'options': ['1', '1/e', '', ''], 'type': 102}
- 设随机变量X的分布律为[img=156x60]180380a9d1bcbc6.png[/img]k=0,1,2,...,n,则a的值为( ). A: 1 B: [img=25x22]180380a9da7f0aa.png[/img] C: [img=27x23]180380a9e29f140.png[/img] D: [img=17x23]180380a9ec56033.png[/img]
内容
- 0
设随机变量X的分布律为[img=156x60]1802f2a63c05e74.png[/img]k=0,1,2,...,n,则a的值为( ). A: 1 B: [img=25x22]1802f2a643d9f81.png[/img] C: [img=27x23]1802f2a64c7b875.png[/img] D: [img=17x23]1802f2a6549029c.png[/img]
- 1
设随机变量X的分布律为[img=156x60]180339573cd6579.png[/img]k=0,1,2,...,n,则a的值为( ). 未知类型:{'options': ['1', '', '', ''], 'type': 102}
- 2
设随机变量X的分布律为[img=377x76]1802e8d4e90c083.png[/img]则E(X)= ( ). A: 0 B: 1 C: 2 D: 3 E: 不存在
- 3
设随机变量X的分布律为[img=333x68]1803395e66cbb09.png[/img]则E(X)= ( ). A: 0 B: 1 C: 2 D: 不存在
- 4
设随机变量X的分布律为[img=333x68]18031e966ef66a9.png[/img]则E(X)= ( ). A: 0 B: 1 C: 2 D: 不存在